Correlates of immune protection from tuberculosis. - Fletcher, H (2007)
Due to the failure of chemotherapy and the only available vaccine, BCG, to control tuberculosis (TB) disease, there is an urgent need to develop new vaccines and therapeutics. The identification of correlates of immune protection or "biomarkers" will facilitate the rational design of vaccines and drugs for the prevention and clearance of TB infection. Although it is known that IFN-gamma is essential for protective immunity, animal and human studies have found that IFN-gamma alone is not sufficient for the prevention of TB disease. There is evidence that IL-23, a recently described member of the IL-12 family of cytokines, is important in the immuno-pathogenesis of TB. There is also evidence that regulatory T cells (Treg) are present in TB disease and that Treg may suppress effector T cell responses. In the last five years, clinical studies have been able to use Mycobacterium tuberculosis specific antigens, such as ESAT-6, to focus on recently infected, healthy contacts of TB patients in endemic countries. Advances in techniques such as multi-parameter flow cytometry and DNA microarray analysis will enable us to study these cohorts in great detail and facilitate the identification of immune correlates for the rational design of drugs and vaccines for the treatment and prevention of TB.